2003
DOI: 10.1016/s0960-8966(02)00197-9
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac assessment in childhood carriers of Duchenne and Becker muscular dystrophies

Abstract: Cardiac disease in adult female carriers of the X-linked dystrophinopathies, Duchenne and Becker muscular dystrophies, is a wellrecognised entity. A single study has reported a 15% incidence of cardiac abnormalities in female carriers under 16 years. Our study aims, clinically and with electrocardiograph and echocardiograph, to determine the incidence of cardiac abnormality in young girls who are proven carriers of X-linked dystrophinopathies. Twenty-three girls aged 6.2-15.9 years were assessed. All had norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 15 publications
1
37
0
2
Order By: Relevance
“…2,3 It has been estimated that about 8% of DMD female carriers have some manifestations including cardiomyopathy and/or some degree of weakness that could be highlighted by careful clinical examination. [4][5][6][7][8] Relationships between clinical phenotype and dystrophin abnormalities in muscle tissue among female carriers of DMD gene mutations were previously investigated. 9 However, a comprehensive view of factors underlying clinical symptoms occurrence and severity is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 It has been estimated that about 8% of DMD female carriers have some manifestations including cardiomyopathy and/or some degree of weakness that could be highlighted by careful clinical examination. [4][5][6][7][8] Relationships between clinical phenotype and dystrophin abnormalities in muscle tissue among female carriers of DMD gene mutations were previously investigated. 9 However, a comprehensive view of factors underlying clinical symptoms occurrence and severity is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Sixteen per cent had a dilated left ventricle but none had dCMP (29,65,66). In a study of 23 female carriers six to 16 years of age (67), none showed abnormalities on clinical examination, ECG or echocardiography. In a study of 23 carriers (68), CI was found in 63% of individuals.…”
Section: CImentioning
confidence: 97%
“…Studies involving female carriers of mutated dystrophin alleles suggested that levels slightly greater than 50% of normal are protective against skeletal muscle disease (127,538), although other studies of X-linked DCM patients report that levels as low as 30% of normal dystrophin expression can prevent significant skeletal muscle disease (637). The therapeutic threshold in the heart is complicated by the inability to obtain cardiac biopsies to determine the level of expression and by variability in the manifestation of cardiac disease in these patients (288,370,580,649).…”
Section: Dystrophin Gene Transfermentioning
confidence: 99%